Die molekulare Entschlüsselung unkonventioneller Sekretionsmechanismen - Steringer, Julia P.; Müller, Hans-Michael; Nickel, Walter (Biospektrum, 2014)
The vast majority of secretory proteins is characterized by N-terminal signal peptides that allow for co-translational translocation into the lumen of the endoplasmic reticulum, the initial compartment of the classical ER/Golgi-dependent secretory pathway. However, extracellular proteins with fundamental physiological functions in immune surveillance and tissue organization have been identified that lack signal peptides. The molecular mechanisms by which these unconventional secretory proteins reach the extracellular space are beginning to emerge.
Gesehen am 11.12.2020